Mirror Neuron Dalam Pendidikan Islam - Arsyadi, Sidiq; Tursih, Harmi; Dwiparwati, Tanti; Attaqi, Muhammad Inam; Hutasuhut, Efni Fazriah (BELAJEA: Jurnal Pendidikan Islam, 2018)
This study aims to develop a theory of social intelligence or mirror neurons. This study serves to determine the effect of social intelligence in various things. Especially mirror neurons in the perspective of Islamic education. Neuron mirror is a mirror brain, the intention of the mirror brain is the ability of the brain to mimic what he sees and perceives. The working of the mirror brain like Javanese philoshopy is Witing tresna Jalaran Saka Kulina which means that love comes because habitually.So,brain mirror will work to imitate something optimally if done habituation or done continuosly.Mirror neurons in the present era are widely studied because mirror neurons affect the social ability of a person. The results of this study indicate that a good social ability of a person affect the level of social intelligence. Human as social beings interact with each other in various things. Keywords: influence, social brain, mirror neuron